2019
DOI: 10.2478/raon-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Dose-volume derived nomogram as a reliable predictor of radiotherapy-induced hypothyroidism in head and neck cancer patients

Abstract: BackgroundThe aim of this study was to determine the possible predictive value of various dosimetric parameters on the development of hypothyroidism (HT) in patients with head and neck squamous cell carcinoma (HNSCC) treated with (chemo)radiotherapy.Patients and methodsThis study included 156 patients with HNSCC who were treated with (chemo)radiotherapy in a primary or postoperative setting between August 2012 and September 2017. Dose-volume parameters as well as V10 toV70, D02 to D98, and the VS10 to VS70 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Prpic et al 40 analyzed retrospectively 156 patients with head and neck cancer treated with IMRT and showed that thyroid dose parameters VS65, minimum dose (Dmin), and V50 were related to the incidence of hypothyroidism. Sachdev et al 41 suggested that thyroid V50 < 60% should be set as the optimal dose parameter.…”
Section: Radiotherapymentioning
confidence: 99%
“…Prpic et al 40 analyzed retrospectively 156 patients with head and neck cancer treated with IMRT and showed that thyroid dose parameters VS65, minimum dose (Dmin), and V50 were related to the incidence of hypothyroidism. Sachdev et al 41 suggested that thyroid V50 < 60% should be set as the optimal dose parameter.…”
Section: Radiotherapymentioning
confidence: 99%
“…This difference may be related to the follow-up time, sample size, and treatment planning systems. Thyroid V 50 is an important prognostic variable for radiation-induced HT in patients with NPC [23]. For example, Ling et al [24] retrospectively analyzed 102 patients and recommended thyroid V 50 < 50% as the optimal dose-volume limiting threshold for HT after radiotherapy.…”
Section: Hypothyroidism and Thyroid Dosementioning
confidence: 99%
“…Also, the retrospective nature of some studies contributed to this variation. Using 3DCRT alone like our study and El-Sherbiney et al study [16] may contribute to different outcomes than using IMRT in other studies [2,14,15,28].…”
Section: Discussionmentioning
confidence: 55%
“…Our results have shown that the incidence of RIHT after maximum follow up of 24 months was 26%. The range of reported incidence from similar studies ranged from 17-47% [2,5,15,16,18,19]. Our follow up period is relatively short and the incidence is expected to increase with longer follow up periods.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation